1993
DOI: 10.1093/jnci/85.17.1419
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Proliferation-Associated Molecules in Individual Micrometastatic Carcinoma Cells

Abstract: Although support from clinical follow-up is still needed, this study demonstrates that, beyond the mere presence of micrometastatic cells in bone marrow, useful prognostic information can be obtained by analysis of additional cell growth markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
244
1
23

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(279 citation statements)
references
References 19 publications
11
244
1
23
Order By: Relevance
“…Previous studies by Pantel et al (1993), Braun et al (2001a) and Solomayer et al (2006), reported high rates of HER2 overexpression ranging from 60 to 100% of cases, analysed by immunocytochemistry only. These rates could therefore be explained by technical aspects, that is, excessively sensitive immunohistochemistry technique.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies by Pantel et al (1993), Braun et al (2001a) and Solomayer et al (2006), reported high rates of HER2 overexpression ranging from 60 to 100% of cases, analysed by immunocytochemistry only. These rates could therefore be explained by technical aspects, that is, excessively sensitive immunohistochemistry technique.…”
Section: Discussionmentioning
confidence: 91%
“…However, the fate of disseminated cancer cells can be influenced by the qualitative properties of these cells and by several host factors (Heiss et al, 1995a). Studies on disseminated tumour cells in bone marrow offer the possibility of investigating the penultimate step in the development of metastasis and to gain information about the induction and regulation of the ensuing growth (Frassica and Sim, 1988;Pantel et al, 1993;Diel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Pantel et al (1993) investigated the expression of Ki-67, p120 and ErbB2 on micrometastatic breast and gastric cancer cells. They found a high incidence of ErbB2 expression on disseminated breast cancer cells in patients with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Riesenberg et al (1993) detected PSA exclusively on disseminated prostate tumor cells and not in bone marrow cells, which are known to be PSA-negative. The proliferation antigen Ki67 is known to be expressed in bone marrow (Gerdes et al 1984), and Pantel et al (1993b) described positive Ki67 staining of CK18-positive as well as surrounding CK18-negative bone marrow cells. In contrast, the same study did not detect immunogold staining of bone marrow cells for p120, a proliferation marker that is absent in bone marrow (Pantel et al 1993b).…”
Section: Discussionmentioning
confidence: 99%
“…uPA-R as a central representative of the urokinase system, a pattern of factors known to be involved in tumor-associated proteolysis and potentially to represent a tumor cell's invasive capacity (Blasi 1993;Moller 1993), may indicate aggressive phenotypes of disseminated tumor cells. Other parameters also, such as the tyrosin kinase receptor Erb-B2 (Pantel et al 1993b) which is potentially associated with aggressive tumor cell growth, proliferation antigens (Pantel et al 1993b), or tissuespecific antigens such as prostate-specific antigen (PSA) (Riesenberg et al 1993), have already been identified on CK18-positive cells in bone marrow and may help in estimating their biological properties and tumor cell identity.…”
mentioning
confidence: 99%